2023
DOI: 10.7717/peerj.15894
|View full text |Cite
|
Sign up to set email alerts
|

Tibial cortex transverse transport potentiates diabetic wound healing via activation of SDF-1/CXCR4 signaling

Shuanji Ou,
Xiaodong Wu,
Yang Yang
et al.

Abstract: Background The current treatments for diabetic foot ulcers have disadvantages of slow action and numerous complications. Tibial cortex transverse transport (TTT) surgery is an extension of the Ilizarov technique used to treat diabetic foot ulcers, and can shorten the repair time of diabetic foot ulcers. This study assessed the TTT technique for its effectiveness in healing diabetic foot ulcer skin lesions and its related molecular mechanisms. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Using a similar rat model of TTT, another study tried to examine the effect of TTT on DFU and reported positive results. 20 However, the skin defect created was relatively small (4 mm × 5 mm) and hindlimb ischemia was not induced simultaneously. 20 Thus, this model mimicked only mild DFU.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Using a similar rat model of TTT, another study tried to examine the effect of TTT on DFU and reported positive results. 20 However, the skin defect created was relatively small (4 mm × 5 mm) and hindlimb ischemia was not induced simultaneously. 20 Thus, this model mimicked only mild DFU.…”
Section: Discussionmentioning
confidence: 99%
“… 20 However, the skin defect created was relatively small (4 mm × 5 mm) and hindlimb ischemia was not induced simultaneously. 20 Thus, this model mimicked only mild DFU. According to the clinical guideline of TTT treatment, this technique should be applied to severe DFU rather than acute traumatic foot wound or mild DFU considering cost-effectiveness of TTT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations